Evidence-Based Guideline for Treatment of Neurocysticercosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
The Guideline Development Subcommittee of the AAN conducted a literature search and review of 10 Class I or Class II trials of treatment for parenchymal neurocysticercosis.